Knowledge, attitude and preventive practices of sexually transmitted infections among unmarried youths in an urban community in Lagos State, Nigeria - Esther O. Oluwole; Oluwatobiloba D. Oyekanmi; Doyin O. Ogunyemi; Gbemisola E. Osanyin (AOSIS, 2020)
Background: Sexually transmitted infections (STIs) are of public health importance as over 1 million STIs are acquired daily worldwide. One-third of the new cases of curable STIs affect younger persons aged less than 25 years. Sexually transmitted infections can lead to severe complications beyond the immediate impact of infections as such. Aim: This study assessed knowledge of, attitude towards and preventive practices of STI among young unmarried persons in Surulere local government area (LGA) of Lagos State, Nigeria. Setting: The study was conducted among young unmarried persons in Surulere LGA, Lagos State, Nigeria, between June and November 2018. Methods: A descriptive cross-sectional study was conducted among 450 young unmarried persons selected using a multistage sampling technique. An interviewer-administered questionnaire was used to obtain data. Analysis was carried out with Epi-Info 7.2.2.2 software. Chi-square was used to test for associations. Level of significance was at p ≤ 0.05. Results: The mean age was 19.9 + 2.5 years. Majority of the respondents (84.7%) had heard of STIs. About two-third (65.6%) had good knowledge, while majority (98.6%) had good attitude towards the prevention of STIs, but less than half (34.0%) had good preventive practices. Knowledge of STI was statistically significantly associated with age, level of education, attitude and preventive practices of the respondents. Conclusion: Most of the respondents were aware and had good attitude towards prevention of STI, but gaps exist in knowledge and preventive practices. Hence, targeted education to improve the knowledge and preventive practices against STI among young unmarried persons is recommended.